2017
DOI: 10.1111/bjh.14513
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: routes to diagnosis, clinical characteristics and survival – findings from a UK population‐based study

Abstract: SummaryPrompt cancer diagnosis may align UK survival with European averages. We examined the impact of route to diagnosis on survival for multiple myeloma patients diagnosed 2012–2013 using data from our population‐based patient cohort that links to national death notifications and collects details on treatment and response (n = 441). Emergency presentation was associated with advanced disease and poorer outcomes, and was the commonest route to diagnosis (28·1%) followed by General Practitioner urgent (19·0%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 13 publications
(16 reference statements)
1
40
0
2
Order By: Relevance
“…It is, however, challenging to compare the characteristics of the study population with those from other European population-based studies owing to differences in the parameters reported. 16,21 A relatively high proportion of patients scored III using the ISS at diagnosis compared with other studies, 16,21 although high ISS stages are associated with poor survival and would be expected in a population of now deceased patients. 22 Furthermore, only one-quarter of patients had a history of skeletal-related events; this is lower than would be expected because bone disease occurs in 80% of patients with newly diagnosed MM.…”
Section: Discussionmentioning
confidence: 94%
“…It is, however, challenging to compare the characteristics of the study population with those from other European population-based studies owing to differences in the parameters reported. 16,21 A relatively high proportion of patients scored III using the ISS at diagnosis compared with other studies, 16,21 although high ISS stages are associated with poor survival and would be expected in a population of now deceased patients. 22 Furthermore, only one-quarter of patients had a history of skeletal-related events; this is lower than would be expected because bone disease occurs in 80% of patients with newly diagnosed MM.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between late diagnosis and poor outcome is recognised for many cancers, with delay often resulting in more advanced disease, worse survival, increased risk of complications, and impaired quality of life. [1][2][3] Hence, over recent decades the UK Department of Health has introduced a series of interventions aimed at facilitating earlier diagnosis. In primary care settings, this includes referral guidance to aid GP identification of cancer symptoms and the introduction of suspected cancer pathways to minimise time to specialist secondary care consultation.…”
Section: Introductionmentioning
confidence: 99%
“…Among haematological cancers (lymphomas, myelomas and leukaemias), emergency presentation is relatively common [10], [11]. While this is clearly the appropriate route for conditions like the acute leukaemias, the reasons why a relatively large proportion of patients with non-Hodgkin lymphomas (NHL) present as an emergency and have poorer survival is less obvious.…”
Section: Introductionmentioning
confidence: 99%